Pengembangan Platform Kelayo dengan Metode Design Thinking untuk Meningkatkan Pengalaman Wisata - Anthony, Dicky; Nisa, Ulfatun; Muhibbullah, Aminudin; Fikri, Muhamad Ahdi Nur; Desty, Excel Ervina; Adharin, Mutiara Nabila (Journal of Information System Research (JOSH), 2024)
Kelayo platform was developed to address common problems faced by tourists in Yogyakarta, such as the difficulty of obtaining complete and reliable information about tourist destinations, as well as the risk of fraud from unverified services. This research aims to enhance the tourist experience by providing a digital solution that integrates accommodation, transportation, and tour guide services into a single platform. The methodology used is Design Thinking, which includes the stages of Empathize, Define, Ideate, Prototype, and Test. Research data were collected through observations and interviews with tourists and local tourism stakeholders. The interview results were used to identify the main needs and problems that formed the basis for the development of the application's features. The study results indicate that the implementation of the Kelayo platform can reduce trip planning time by up to 35%, with an increase in user satisfaction reflected by a score of 80 on the System Usability Scale (SUS) evaluation. Additionally, the service verification feature reduces the risk of fraud by up to 50%, providing a sense of safety and convenience for users. The main contribution of this research is to offer a digital-based solution that improves transparency and efficiency in the tourism industry in Yogyakarta. Further development recommendations include involving a broader range of users and continuous testing to ensure the platform's relevance to the dynamic needs of tourists. This research demonstrates that the Design Thinking method is effective in designing an intuitive user interface that meets user needs.